Fractional and Integer Order Chaotic System-based Pseudo Random Bit Generator for Secure Image Encryption - Ince, Esra; Karakaya, Baris; Turk, Mustafa (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper presents an implementation of continuous-time chaotic system-based pseudo random bit generation by using fractional order Chen-Lee and integer order Lorenz systems. Since chaotic systems are very popular in random bit generator applications, both fractional and integer order chaotic systems are used in the proposed design. The electronic circuit equivalence of chaotic systems are designed and simulated in Orcad-Pspice environment to use as an entropy source to the proposed a new post-processor algorithm. The generated random bit stream is tested by using NIST 800.22 statistical test suite to demonstrate the randomness of the proposed system statistically. Also, an image encryption application is executed using a pseudo random bit stream. The results of the statistical tests and image encryption show that the proposed pseudo random bit generator is suitable and can be preferred in secure image/media transmission/communication systems. © 2022 IEEE.
13th National Conference with International Participation, ELECTRONICA 2022 -- 19 May 2022 through 20 May 2022 -- Sofia -- 182635
Keywords: chaos; fractional order; image encryption; pseudo random bit; statistical tests